Analisis Perbandingan Material Plat Stainless Steel 304 Dengan Graphite Sheet Dalam Produksi Gas Hidrogen Pada Generator Dry Cell - Danu Darma Wijaya; R. Mohammad Alansyah Mauludi; Arif Putra Pratama; Delvis Agusman; Hendi Saryanto (Prosiding Seminar Nasional Teknoka, 2022)
Energy are the most important part of human life, every activity in human life is dependent on energy consumption. Humans are now using fossil fuel energy sources on a large scale so that fuel (fuel oil) is running low and alternative energy is needed. Hydrogen gas is an alternative energy that can replace fossil energy sources by using the electrolysis process in dry cell generators. The research aims to determine the material with the highest production and highest efficiency in the electrolysis process. This study used an experimental method by comparing stainless steel material with graphite sheets. From the results of the study it was concluded that the highest production rate was obtained for the variation of stainless steel 304 plate material at a time variation of 30 seconds with a result of 0.013333 l/s and the lowest variation for graphite sheets. at a time variation of 90 seconds with a result of 0.002222 l/s. The highest efficiency was obtained from variations in Stainless steel material with a time of 30 seconds reaching an efficiency of 45.19% and the lowest was obtained from variations of Graphite sheet with a time variation of only 7.53%.